PRODUÇÃO DE FORRAGEM DE AVEIA INFLUENCIADA PELA ADUBAÇÃO E MANEJO - Primavesi, Ana Cândida; Primavesi, Odo; Cantarella, Heitor; Godoy, Rodolfo (REVISTA DE AGRICULTURA, 2015)
PRODUÇÃO DE FORRAGEM DE AVEIA INFLUENCIADA PELA ADUBAÇÃO E MANEJO